Emotional intelligence and recovering from induced negative emotional state - Limonero, Joaquín T.; Fernández-Castro, Jordi; Soler-Oritja, Jordi; Álvarez-Moleiro, María (Frontiers in Psychology, 2015)
The aim of the present study was to examine the relationship between emotional intelligence and recovering from negative emotions induction, using a performance test to measure Emotional Inteligence (EI). Sixty seven undergraduates participated in the procedure, which lasted 75 minutes and was divided into three stages. At Time 1, subjects answered the STAI-S, POMS-A, and EI was assessed by MSCEIT. At Time 2, negative emotions were induced by 9 pictures taken from the International Affective Picture System (IAPS) and participants were asked to complete a second STAI-S and POMS-B questionnaires. At Time 3 participants were allowed to rest doing a distracting task and participants were asked to complete a third STAI-S and POMS-A questionnaires. Results showed that the branches of the MSCEIT emotional facilitation and emotional understanding are related to previous mood states and mood recovery, but not to mood reactivity. This finding contrasts nicely with studies on which emotional recovery was assessed in relation to EI self-reported measures, highlighting the perception and emotional regulation.